Comprehensive histopathological diagnostics of aggressive B-cell lymphomas based on the updated criteria of the World Health Organisation’s 2017 classification - Szumera-Ciećkiewicz, Anna; Rymkiewicz, Grzegorz; Grygalewicz, Beata; Jesionek-Kupnicka, Dorota; Gruchała, Andrzej; Ziarkiewicz-Wróblewska, Bogna; Gałązka, Krystyna; Reszeć, Joanna; Borg, Katarzyna; Prochorec-Sobieszek, Monika (Polish Journal of Pathology, 2018)
Revision of the fourth edition of the World Health Organisation (WHO) Classification of Haematopoietic and Lymphatic Tissues, which was published in 2017, introduced important changes updating the biology, pathology, genetics, and clinical presentation of aggressive B-cell lymphomas. High grade B-cell lymphomas (HGBLs) replaced B-cell lymphoma, unclassifiable, with features intermediate between diffuse large B-cell lymphoma and Burkitt lymphoma, the new provisional entity Burkitt-like lymphoma with 11q aberration was identified, and some categories were upgraded, e.g. EBV-positive diffuse large B-cell lymphoma, not otherwise specified. Still the histopathological diagnostics is based on morphology and immunoprofile, but to define the HGBLs evaluation of MYC, BCL2, and BCL6 gene statuses is required. According to the presented WHO criteria, in the comprehensive histopathological diagnostics of aggressive B-cell lymphomas a highly specialised diagnostic team including a pathologist, a molecular biologist, a geneticist, a haematologist, and immunophenotyping technicians is needed.